Analyzing Organization-to-project Interfaces in the Integration Management of Engineering Projects. (December 2019) - Yu, Jialu; Yang, Qing; Yang, Na
Abstract: To carry out the construction project management work effectively, the organization interface management in the workflow is a fundamental challenge.In the ongoing project, multiple project teams need to cooperate multi-party andcomplete project product delivery in different work interfaces. Organizational interface withinworkflow will help system planning and management in the engineering field. In this study, we first propose the evaluation indicators of engineering participants and tie strength between different organizations usingthe design structure matrix (DSM). Then we construct a multi-domain matrix (MDM) based on organization-to-project by correlating multiple participants in the project with the workload completion degree and present a comprehensive strength between the organization and the project to identify the crucial project interface.Finally, we give an engineering case to illustrate the proposed method and discuss its practical value. The proposed methods reinforce several managerial practicesfor the construction organization and project arrangement.